PENGARUH MEDIA SOSIAL DAN AFILIASI PENJUAL TERHADAP BRAND EQUITY PADA UMKM DI KOTA LHOKSEUMAWE - Abdullah, Abdullah; Bustami, Koko; Yusuf, Yafitzam; Hendiyani, Dina; Saifrizal, Muhammad (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine the influence of social media and seller affiliation on brand equity. Data was collected using a questionnaire to 102 MSME samples in Lhokseumawe City and analyzed by multiple linear regression method. The results show that social media and seller affiliation have a significant influence both partially and simultaneously on brand equity. Social media has a dominant influence on brand equity with a tcount value of 3.105 which is greater than the ttable value of 1.29007 with a significance level of 0.002. The seller's affiliation also had a significant influence with a tcount value of 12.224 which was greater than the ttable value of 1.29007 with a significance level of 0.002. The simultaneous influence between social media and seller affiliation was also significant with a value of Fcal 93.350 which was greater than the value of Ftable 3.09 with a significance level of 0.000. These results show that marketing strategies that are integrated with social media and seller affiliates can increase brand equity